2018
DOI: 10.1021/acs.jnatprod.8b00431
|View full text |Cite
|
Sign up to set email alerts
|

Semisynthesis of ω-Hydroxyalkylcarbonate Derivatives of Hydroxytyrosol as Antitrypanosome Agents

Abstract: Several lipophilic ω-hydroxyalkylcarbonate hydroxytyrosol derivatives and also their corresponding dimeric derivatives have been synthesized, coupling the primary hydroxy group of this phenolic compound with several terminal diols of different chain lengths, by the use of a carbonate linker. The trypanocidal activity and cytotoxicity of these ω-hydroxyalkylcarbonate derivatives of hydroxytyrosol and known alkylcarbonate derivatives of hydroxytyrosol were assessed. Three of the hydroxytyrosol alkylcarbonate der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…It was demonstrated that HTyr has antitrypanosomal and antileishmanial activity [94]. HTyr alkylcarbonate derivatives were active against Trypanosoma brucei [95]. Trypanosomiasis and leishmaniasis, infectious diseases caused by protozoan parasites, affect millions of people around the world, especially in tropical and subtropical area, and present one of the major causes of hunger and poverty in sub-Sahara Africa.…”
Section: Hydroxytyrosolmentioning
confidence: 99%
“…It was demonstrated that HTyr has antitrypanosomal and antileishmanial activity [94]. HTyr alkylcarbonate derivatives were active against Trypanosoma brucei [95]. Trypanosomiasis and leishmaniasis, infectious diseases caused by protozoan parasites, affect millions of people around the world, especially in tropical and subtropical area, and present one of the major causes of hunger and poverty in sub-Sahara Africa.…”
Section: Hydroxytyrosolmentioning
confidence: 99%
“…For example, esterification reactions, coupled with protection and deprotection of hydroxyl groups, have been performed to achieve the formation of ω-hydroxyalkylcarbonate derivatives starting from HTyr (Scheme ). These derivatives showed increased antimicrobial activity against Tripanosoma brucei compared to HTyr.…”
Section: Polyphenols Found In Olea Europaea Lmentioning
confidence: 99%
“…The synthesis of alkyl carbonate derivatives of hydroxytyrosol is strategic to increase hydroxytyrosol antioxidant activity [ 272 ]. Carbonate derivatives have been achieved by a multi-step process in which the chloroformate hydrxytyrosol derivative (having protected phenolic groups) was reacted with alkyl alcohols or diols of different chain lengths [ 272 , 273 ] ( Scheme 24 ). Hydroxytyrosyl carbonates also exhibited higher anti-trypanosome activity against Trypanosoma brucei with respect to the precursor [ 273 ].…”
Section: Diphenolsmentioning
confidence: 99%